Measure of the Rule. - Barr, Robert (Heritage., 1973)
The Measure of the Rule, originally published in 1907, is the nearest Robert Barr came to writing an autobiographical novel. It concerns the Toronto Normal School and the experiences there in the 1870s of a young man who undoubtedly is Barr himself.